2014
DOI: 10.1152/ajprenal.00010.2014
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of kidney function by the (pro)renin receptor blocker handle region peptide in aliskiren-treated diabetic transgenic (mRen2)27 rats

Abstract: Dual renin-angiotensin system (RAS) blockade in diabetic nephropathy is no longer feasible because of the profit/side effect imbalance. (Pro)renin receptor [(P)RR] blockade with handle region peptide (HRP) has been reported to exert beneficial effects in various diabetic models in a RAS-independent manner. To what degree (P)RR blockade adds benefits on top of RAS blockade is still unknown. In the present study, we treated diabetic TGR(mREN2)27 rats, a well-established nephropathy model with high prorenin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The putative (P)RR blocker HRP did not provide add-on beneficial effects when combined with aliskiren, nor counteracted the effects of aliskiren in the retina of diabetic mRen2 rats. The latter contrasts with earlier observations in the kidney of diabetic mRen2 rats, where HRP counteracted the beneficial effects of aliskiren [47]. The former agrees with our in-vitro studies in Müller cells, showing prorenin-induced effects that are entirely Ang II-dependent.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The putative (P)RR blocker HRP did not provide add-on beneficial effects when combined with aliskiren, nor counteracted the effects of aliskiren in the retina of diabetic mRen2 rats. The latter contrasts with earlier observations in the kidney of diabetic mRen2 rats, where HRP counteracted the beneficial effects of aliskiren [47]. The former agrees with our in-vitro studies in Müller cells, showing prorenin-induced effects that are entirely Ang II-dependent.…”
Section: Discussionsupporting
confidence: 57%
“…STZ-induced diabetes mellitus increased blood glucose levels ∼5-fold, and treatment with aliskiren or aliskiren+HRP did not alter this. Aliskiren lowered MAP in Ren2 rats from 123±4 mmHg to 104±5 mm Hg, and this effect was unaltered by simultaneous administration of HRP [47].…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, HRP does not show a protective effect in the clipped kidney, Goldblatt hypertensive rat model (Krebs, et al, 2008). Moreover, in diabetic TGR(mREN2)27 rats, a well-established nephropathy model characterized by high prorenin levels, HRP was shown to counteract the beneficial effects of aliskiren in the kidney, induce hyperkalemia, and increase plasma plasminogen activator-inhibitor 1, renal COX-2, and cardiac collagen content (te Riet, et al, 2014). A recent study showed that HRP may actually have an agonistic effect upon binding to the PRR, increasing phosphorylation of ERK1/2 in the retina (Wilkinson-Berka, Heine, et al, 2010).…”
Section: The Development Of Prr Antagonistsmentioning
confidence: 99%
“…In contrast, only ACE inhibition could ameliorate ERK1/2 phosphorylation. It has been reported that HRP might also exert partial agonist effect on (P) RR, apart from the receptor blockade [34]. This could explain why HRP did not influence the diabetes-induced ERK phosphorylation in our study.…”
Section: Discussionmentioning
confidence: 41%